Line‐field confocal optical coherence tomography—Practical applications in dermatology and comparison with established imaging methods. Issue 3 (21st October 2020) - Ruini, Cristel; Schuh, Sandra; Sattler, Elke; Welzel, Julia
Abstract: Background: Non‐invasive diagnostic techniques in dermatology gained increasing popularity in the last decade. Reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) are meanwhile established in research and clinical routine. While OCT is mainly indicated for detecting non‐melanoma skin cancer, RCM has proven its usefulness additionally in distinguishing melanocytic lesions. Line‐field confocal optical coherence tomography (LC‐OCT) is an emerging tool combining the principles of both above‐mentioned methods. Methods: Healthy skin at different body sites and exemplary skin lesions (basal cell carcinoma, malignant melanoma, actinic keratosis) were examined using dermoscopy, RCM, OCT and LC‐OCT. Standard features for RCM and OCT and comparable features for LC‐OCT were analysed. Results: LC‐OCT has a lower penetration depth but superior resolution compared to OCT. In comparison with RCM, which provides only horizontal sections, LC‐OCT creates both vertical and horizontal images in real time and has nearly the same cellular resolution. Discussion: Our preliminary experiences suggest that LC‐OCT combines the advantages of RCM and OCT, with optimal resolution and penetration depth to diagnose all types of skin cancer. Larger systematic studies are needed to further characterize the field of use of this device and its sensitivity and specificity compared to histology.